2007
DOI: 10.21236/ada604853
|View full text |Cite
|
Sign up to set email alerts
|

The Eigenfunction of the Reed-Muller Transformation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…A truth vector satisfying the equation RM·F = F is an eigenvector of RM with the eigenvalue λ = 1 [5], [7]. To find the eigenvectors, the eigenvalues are needed first, which may be calculated by using the characteristic polynomial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A truth vector satisfying the equation RM·F = F is an eigenvector of RM with the eigenvalue λ = 1 [5], [7]. To find the eigenvectors, the eigenvalues are needed first, which may be calculated by using the characteristic polynomial.…”
Section: Discussionmentioning
confidence: 99%
“…Eigenvectors of the Reed Muller Transformation for the binary case were studied in [5]. The present paper may be considered a further step in that line of research.…”
Section: Introductionmentioning
confidence: 93%
“…The Preparata (Reed-Müller) Transformation (Preparata, 1964;Saluja and Ong, 1979;Green, 1987;1994;Stankovic et al, 1996;Kim et al, 1999;Quintana and Avedillo, 2001;Sasao and Butler, 2007;Rushdi and Ghaleb, 2013) for a Boolean function …”
Section: Preparata Transformationmentioning
confidence: 99%
“…The eigenvector x for any matrix M is calculated using the characteristic equation , where is the eigenvalue for matrix M. The eigenvectors and eigenvalues of RMT follow the definition given below, as mentioned in [7]. The RMT matrix R(n) can be decomposed using the kronecker product as given by (9).…”
Section: Eigen Vector Decomposition Of Reed-muller Transform (Rmt)mentioning
confidence: 99%
“…Since Reed-Muller transform is so widely used, it will be useful to find algorithms to perform its eigen-decomposition. Eigenfunctions of Reed-Muller Transform were introduced by Sasao and Butler in [7]. The work identified three symmetric functions with certain special properties and showed that these symmetric functions can be found among the eigenfunctions of the Reed-Muller transform.…”
Section: Introductionmentioning
confidence: 99%